A re-assessment of house price indices: evidence from the Spanish market - Taltavull de la Paz, Paloma; McGreal, Stanley (International Journal of Strategic Property Management, 2019)
This paper using evidence from the Spanish housing market contributes significantly to the debate concerning the different results obtained from house price indices depending on the method used to build the index. Utilising a large database over the period 1994 to 2012, the paper constructs a time dummy hedonic index (HD) and an imputed hedonic index using a Laspeyres approach (HI), and compares the different effect on the price index evolution. The paper discusses control by quality changes and identifies those attributes experiencing structural changes over the analysis period, identified by the HI index but not by the HD index. Results indicate that changes in quality stem from socio-demographic conditions rather than changes to housing quality (other than size). The paper also shows that improvements in neighbourhood quality rather than change in a ‘typical house’ affects house price and argues that these considerations are important in both the method selected to calculate house price indices and the application of the methodology to estimate price changes. First Published Online: 30 Nov 2018